2023
DOI: 10.3390/plants12020415
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS Analysis and Antifungal Activity of Turnera subulata Sm.

Abstract: Fungi of the Candida genus are responsible for invasive candidiasis, which affects people all over the world and has high mortality rates. This is due to their virulence factors, which give them great resistance and pathogenicity. In addition, the emergence of multidrug-resistant strains makes it difficult to treat these infections. In this way, natural products have emerged as an alternative to standard drugs, where plants known for their medicinal properties such as Turnera subulata become attractive to rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They found that the extract does not have significant activity since an IC 50 of 7544 µg/mL was obtained for C. albicans, while for Candida krusei it was 16,087.37 µg/mL. Similarly, the extract could only inhibit hyphal formation in C. albicans and Candida tropicalis at high concentrations [102].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…They found that the extract does not have significant activity since an IC 50 of 7544 µg/mL was obtained for C. albicans, while for Candida krusei it was 16,087.37 µg/mL. Similarly, the extract could only inhibit hyphal formation in C. albicans and Candida tropicalis at high concentrations [102].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Another relevant biological aspect of the compounds isolated from Turnera subulata is their ability to inhibit and/or eliminate Gram-positive and Gram-negative bacteria and fungi [64][65][66]. This antimicrobial activity of the plant is related to the presence of polyphenols, terpenoids, and essential oils [67].…”
Section: Turnera Subulatamentioning
confidence: 99%